HUMAN RESOURCE COMPETENCIES, SOCIALIZATION, AND READINESS OF MSME ACTORS ON THE IMPLEMENTATION OF FINANCIAL ACCOUNTING STANDARDS FOR MICRO, SMALL AND MEDIUM ENTITIES - Utami, Putri Prameswari; Indrawati, Novita; Rofika, Rofika (Riau International Conference on Economics, Business and Accounting, 2024)
The purpose of this research is to analyze the effect of human resource competence, socialization of SAK EMKM, and the readiness of MSME actors on the implementation of SAK EMKM on MSMEs in Siak Regency. This research is quantitative research, using primary data and measured using a Likert scale. The sample of this research used random sampling technique using the slovin formula and obtained a sample of 126 respondents. Primary data is processed using multiple regression analysis using IBM SPSS Version 26. The results obtained from this research state that the competence of human resources and the readiness of MSME actors have a positive and significant effect on the implementation of SAK EMKM while the socialization of SAK EMKM has no positive and significant effect on the implementation of SAK EMKM.